Utilizing Blended Learning as an Innovation in Arabic Language Teaching Assessment in the Society 5.0 Era - Khabibatun Nisa'; M. Yunus Abu Bakar (Raja Zulkarnain Education Foundation, 2026)
This study aims to examine the utilization of the blended learning model as a strategic innovation in the assessment system of Arabic language learning in the era of Society 5.0, which emphasizes the integration of technology and human values. The research was conducted in Class 4B of MI Miftahul Huda Blongko, Ngetos, Nganjuk during the second semester of the 2024/2025 academic year. The population consisted of all students in Class 4B, with a sample of 17 students selected through total sampling. This study employed a descriptive qualitative approach with data collection instruments including observation, teacher interviews, documentation of learning activities, and analysis of student learning outcomes via digital platforms. Data were analyzed using Miles and Huberman’s interactive analysis model: data reduction, data display, and conclusion drawing. The findings revealed that blended learning plays a crucial role in transforming the Arabic language assessment system from a purely cognitive focus to a more holistic evaluation encompassing affective and psychomotor domains. The use of digital tools such as discussion forums, multimedia assignments, and interactive quizzes supports an objective, transparent, and continuous assessment process. Moreover, digital learning data enables personalized assessment based on individual student achievement and potential. However, the implementation of blended learning still faces challenges, including limited infrastructure, low teacher digital literacy, and insufficient technical support. Therefore, ongoing teacher training and collaboration among teachers, students, and parents are essential to optimizing blended learning as an innovative assessment approach for Arabic language learning in elementary madrasah education.